(3GdbUjOI GdMQHGhjIs - (3YKeGf Hf YjSi Hf efUhQ GdHdWj, JGL GdOjf CHh GdaJM,J (B599 (3g` s
(3ChdgG (B:s
(3Efi CeQD dGjWjHfi GdTGOf GdMSf GdbhGe s
(3BNQgG (B:s
(3hEfi hOOJ hbO SFeJ GdYjTdh jOfh Mede bGd fGXegG YKeGf Hf YjSi GdHdWi (B: (3EfeG SejJgG GdMQHGhjI dCfgG JJdhf Jdhf GdMQHGA , agi eQahYI heQI efUhHI heQI eLQhQI heQI SGcfI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS hGdYTQhfs
(3GdfSNI HgG MhGTs
(3hgj bUjOI YOJgG KdGKI hKdGKhf HjJkG JfTO bGajJgG HGdQaY hGdfUH hGdLQ hGdSchfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1337s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs